IMPLEMENTASI SOLENOID VALVE PADA ALAT PEMBUATAN SANDWICH ANEKA RASA BERBASIS PROGRAMMABLE LOGIC CONTROLLER - Orliana, Sherli; Listiana, Reni (Jurnal TEDC, 2025)
In the era of Industry 4.0, automation in production processes is crucial for improving efficiency, consistency, and product quality. This research aims to design and implement an automated system for the production process of various-flavored sandwich using solenoid valves controlled by a Programmable Logic Controller (PLC). The system is designed to automate the dispensing of different flavored spreads, such as chocolate, strawberry, and blueberry, which are to be precisely applied to the sandwich. This tool utilizes solenoid valves as the main actuators to control the flow of the spread according to the selected flavor. The PLC system acts as the control center, receiving input from various sensors to detect the presence of the bread, the number of bread slices, and the desired type of spread. Additionally, the PLC manages the operation of the conveyor and the bread-pushing mechanism, ensuring that each process runs synchronously. The results of this research demonstrate that the designed system can effectively automate the production process of various-flavored sandwich. The use of solenoid valves controlled by the PLC enhances precision in spread dispensing, reduces human error, and increases production speed. This system is also designed with flexibility, allowing for the adjustment of various production parameters as needed. Overall, the implementation of automation in the sandwich production process can significantly contribute to increased efficiency and quality in the food industry. Thus, this system is expected to be widely adopted in the industry to improve productivity and the quality of the final product.